Demystifying Organizational Health: What Is It And Why Does It Matter? - Fatima Momin; Tanvi Joshi; Chelsea Alasa-As (Journal of Innovation in Polytechnic Education)
As organizations seek to develop high-level leadership skills, improve employee engagement and work towards long-term growth, the theory and application of organizational health has begun to gain increasing importance both in the business world and in academia. This article provides an overview of key concepts of organizational health by dismantling commonly held myths on the topic. It emphasizes the role of leadership, growth mindset, creativity, innovation, psychological safety and vulnerability-based trust in this process. Maintaining consistency across these practices is critical to gaining long-term results. Benefits of organizational health include psychologically empowered employees, increased employee engagement, improved communication, strong leadership, higher profits and sustainable organizational growth. The article concludes by highlighting the need for the development of organizational health within the Canadian context, particularly for marginalized groups.